Magnatic tape interfaces for a dual-parameter coincidence experiment - Sulaiman, M. Yusof; Thomas , R. N. (Elsevier, 1979)
Two dual-parameter interfaces lor nuclear coincidence experiments are described. One of them is used for interfacing the coincidence section to a magnetic tape transport. The other is used for reading the data from the magnetic tape into a multichannel analyzer. Options were provided to enable corrections of the undesired contributions from coincidence with the Compton background and also with the chance events. Tests on the system have shown that both systems arc very efficient and reliable. The interfaces make use of integrated circuits and can therefore be built cheaply.